Segmental and suprasegmental encoding of speaker confidence in Wuxi dialect vowels - Ji, Yujie; Hu, Yanbing; Jiang, Xiaoming (Frontiers in Psychology, 2022)
Wuxi dialect is a variation of Wu dialect spoken in eastern China and is characterized by a rich tonal system. Compared with standard Mandarin speakers, those of Wuxi dialect as their mother tongue can be more efficient in varying vocal cues to encode communicative meanings in speech communication. While literature has demonstrated that speakers encode high vs. low confidence in global prosodic cues at the sentence level, it is unknown how speakers’ intended confidence is encoded at a more local, phonetic level. This study aimed to explore the effects of speakers’ intended confidence on both prosodic and formant features of vowels in two lexical tones (the flat tone and the contour tone) of Wuxi dialect. Words of a single vowel were spoken in confident, unconfident or neutral tone of voice by native Wuxi dialect speakers using a standard elicitation procedure. Based on linear-mixed effects modeling and parametric bootstrapping testing, the results showed that (1) the speakers raised both F1 and F2 in the confident level (compared with the neutral-intending expression). Additionally, F1 can distinguish between the confident and unconfident expressions; (2) Compared with the neutral-intending expression, the speakers raised mean f0, had a greater variation of f0 and prolonged pronunciation time in the unconfident level while they raised mean intensity, had a greater variation of intensity and prolonged pronunciation time in the confident level. (3) The speakers modulated mean f0 and mean intensity to a larger extent on the flat tone than the contour tone to differentiate between levels of confidence in the voice, while they modulated f0 and intensity range more only on the contour tone. These findings shed new light on the mechanisms of segmental and suprasegmental encoding of speaker confidence and lack of confidence at the vowel level, highlighting the interplay of lexical tone and vocal expression in speech communication.